Modeling Physical Structure as Additional Constraints for Stereoscopic Optical See-Through Head-Mounted Display Calibration - Qian, Long; Winkler, Alexander; Fuerst, Bernhard; Kazanzides, Peter; Navab, Nassir (Adjunct Proceedings of the 2016 IEEE International Symposium on Mixed and Augmented Reality, ISMAR-Adjunct 2016, 2017)
For stereoscopic optical see-through head-mounted display calibration, existing methods that calibrate both eyes at the same time highly depend on the HMD user's unreliable depth perception. On the other hand, treating both eyes separately requires the user to perform twice the number of alignment tasks, and does not satisfy the physical structure of the system. This paper introduces a novel method that models physical structure as additional constraints and explicitly solves for intrinsic and extrinsic parameters of the stereoscopic system by optimizing a unified cost function. The calibration does not involve the unreliable depth alignment of the user, and lessens the burden for user interaction.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Augmented Reality; OST-HMD Calibration and Human Factors; SPAAM